AL-QUR’AN DALAM PANDANGAN SYI’AH - HM HM. Attamimy (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2011)
However Sunni-Shia dichotomy is still felt in most Indonesian Muslims. In fact, not infer¬quently, allegations that the Shiites are in the Islamic cult. However, the deve¬lopment of Shi'ites in the country growing, triggered by the Islamic Revo¬lution in Iran under Ayatollah Khumaini, has eroded little by little these base¬less accusations, so in some places, Muslims, whether Sunni sect embraced, or Shi'ites can live side by side in peace. Misunder-standing that occurred between the two mazhab were one by one can be explained so as can to re¬move the mutual distrust between the two. One described here is the accusation that the Shiites have their own Qur'an different from Muslims in general. This accusation was unfounded because the Qur'an is used in the schools of Shi'a is exactly the same as those used by other Muslims. That they have Muṣḥaf ‘Alī and Fāṭima, it's true but the second position Muṣḥaf was nothing more than commentaries on the Qur'an is not the same as al-Quran. Kata Kunci: Syi’ah, al-Qur’ān, kesalahpahaman, Muṣḥaf ‘Alī, revolusi iran.